Tissue engineering for tendon repair. Issue 8 (24th October 2006) - Bagnaninchi, Pierre-Olivier; Yang, Ying; El Haj, Alicia J; Maffulli, Nicola
Abstract : Tissue engineering aims to induce tissue self-regeneration in vivo or to produce a functional tissue replacement in vitro to be then implanted in the body. To produce a viable and functional tendon, a uniaxially orientated collagen type I matrix has to be generated. Biochemical and physical factors can potentially alter both the production and the organisation of this matrix, and their combination in a dose- and time-dependent manner is probably the key to in vitro engineered tendons. This review discusses the role of these different factors affecting tenocyte growth in a three-dimensional environment in vivo and in vitro, and underlines the future challenge of tendon tissue engineering.